İLKOKUL 4. SINIF ÖĞRENCİLERİNİN İNGİLİZCE DERSİNDE KELİME ÖĞRENMEDE FARKLILAŞTIRILMIŞ ÖĞRETİMİN ETKİLERİ - EKİCİ, BURCU (Fırat Üniveristesi, 2024)
Bu araştırmanın genel amacı, ilkokul 4. sınıf öğrencilerinin İngilizce dersinde kelime öğrenmede farklılaştırılmış öğretimin, akademik başarı, öğrenilenlerin kalıcılığı ve öğrenci algıları üzerindeki etkilerini belirlemektir. Araştırma, 2023-2024 Eğitim-Öğretim yılında İzmir ilinde bulunan özel bir ilkokulda öğrenim gören 4. sınıf öğrencileri üzerinde yürütülmüştür. Ön-test - son-test kontrol gruplu yarı deneysel modelde yürütülen araştırmanın örneklemi; 22 deney, 22 kontrol grubunda yer almak üzere toplam 44 öğrenciden oluşturulmuştur. Araştırmada bağımsız değişken olan farklılaştırılmış öğretimin uygulandığı deneysel işlem süreci toplam beş hafta sürmüştür. Veriler, İngilizce Dersi Akademik Başarı Testi, Farklılaştırılmış Öğretim Anketi ve Öğrenci Bilgi Formu ile toplanmıştır. İngilizce Dersi Akademik Başarı Testi, deneysel işlemden önce ön-test ve deneysel işlemden sonra ise son-test ve kalıcılık testi olarak her iki gruba uygulanmıştır. Farklılaştırılmış Öğretim Anketi ise deneysel işlemden önce ve deneysel işlemden sonra olacak şekilde sadece deney grubuna uygulanmıştır. Toplanan veriler, SPSS paket programı aracılığıyla betimsel istatistiki tekniklerden aritmetik ortalama, standart sapma, eta-kare ile bağımsız ve bağımlı gruplar "t" testi ile analiz edilmiştir. Araştırmada elde edilen bulgulara göre, deney ve kontrol grubu öğrencilerinin İngilizce dersi Bütçe Planlama ve İklim Değişikliği Ünitelerindeki kazanımlarına yönelik son-test akademik başarı puanları arasında anlamlı fark bulunamamıştır. Araştırmada bunun olası nedeni, uygulama esnasında öğrencilerin derse devam ile sınavlara kısmi katılımlarına bağlı veri kayıpları ve yine öğrencilerin, deneysel süreçte beklenen bilişsel ve duyuşsal katılımı gösterememelerine bağlı olabileceği şeklinde değerlendirilmiştir. Ancak deney ve kontrol grubu kıyası olmadan, sadece deney grubunun ön-test ile son-test akademik başarı puanları arasında, son test lehine anlamlı fark belirlenmiştir. Araştırmada bu bulgu, farklılaştırılmış öğretimin, İngilizce dersinde kelime öğretiminde etkili olduğu şeklinde değerlendirilmiştir. Ayrıca deney grubu ile kontrol grubu kalıcılık (direnç) test puanları arasında, deney grubu lehine anlamlı fark belirlenmiştir. Bu durum, farklılaştırılmış öğretimin İngilizce kelime öğretiminde kalıcılığı desteklediği şeklinde değerlendirilmiştir. Bunlara ilave olarak, deney grubu öğrencilerinin farklılaştırılmış öğretime yönelik görüşlerinin ve algılarının hem olumlu hem de olumsuz duyguları kapsayan iki farklı eksende toplandığı tespit edilmiştir; bu görüşlerin ve algıların deneysel süreçte fazla değişim göstermemiş olduğu belirlenmiştir.

The general purpose of this research is to determine the effects of differentiated instruction in vocabulary learning in the English class of 4th grade primary school students on academic success, permanence of what has been learned, and student perceptions. The research was conducted on 4th grade students studying at a private primary school in Izmir in the 2023-2024 academic year. The sample of the research conducted in a quasi-experimental model with pretest-posttest control group consisted of a total of 44 students, 22 in the experimental group and 22 in the control group. The experimental procedure in which differentiated instruction, which is the independent variable in the research, was applied lasted a total of five weeks. Data were collected through the English Course Academic Achievement Test, Differentiated Instruction Survey and Student Information Form. English Course Academic Achievement Test was applied to both groups as a pre-test before the experimental procedure and as a post-test and permanence test after the experimental procedure. The Differentiated Instruction Survey was applied only to the experimental group, before and after the experimental procedure. The collected data were analyzed using descriptive statistical techniques such as arithmetic mean, standard deviation, eta-square and independent and dependent groups "t" test through the SPSS package program. According to the findings of the study, it wasn't found that there was a significant difference between the post-test academic achievement scores of the experimental and control group students regarding their achievements in the Budget Planning and Climate Change Units of the English course. In the study, it was evaluated that the possible reason for this might be data losses due to the attendance of the students in the lesson and their partial participation in the exams during the implementation and the inability of the students to show the expected cognitive and affective participation in the experimental process. However, it was determined that there was a significant difference in favor of the post-test only between the pre-test and post-test academic achievement scores of the experimental group students regarding their achievements in the Budget Planning and Climate Change Units of the English course without the comparison of the experimental and control group students. In the study, this finding was evaluated as differentiated instruction was effective in teaching vocabulary in English lessons. In addition, it was indicated that there was a significant difference between the resistance-test academic achievement scores of the experimental and control group students regarding their vocabulary learning gains in favor of the experimental group. This situation was evaluated as differentiated instruction supported permanence in English vocabulary teaching. Furthermore, it was established that the opinions and perceptions of the experimental group students regarding differentiated instruction were gathered on two distinct axes, encompassing positive and negative sentiments; these opinions and perceptions did not change much during the experimental process.
The effects of differentiated instruction on vocabulary learning of primary school 4th grade students in English class
Keywords: Eğitim ve Öğretim